A pilot study of pharmacokinetically guided dosing of oral methotrexate in the initial phase of psoriasis treatment - Hroch, Miloš; Chládek, Jaroslav; Šimková, Marie; Vaněčková, Jaroslava; Grim, Jiří; Martínková, Jiřina (Journal of the European Academy of Dermatology and Venereology, 2008)
BACKGROUND: Clinical studies of low-dose oral methotrexate (MTX) in the treatment of psoriasis and rheumatoid arthritis document a large interpatient variability in the pharmacokinetics of MTX, including its polyglutamates (MTXPGs) in erythrocytes (RBC). This can be a factor contributing to the variability of therapeutic and toxic effects. AIM: This pilot trial aimed to investigate the MTXPG concentrations in RBC as well as their relation to therapeutic and adverse effects during the initial 4 months of pharmacokinetically guided therapy with a divided-dose schedule (three doses of MTX separated by 12-h intervals once a week). SUBJECTS AND METHODS: Sixteen psoriatic patients (4 men and 12 women; mean age, 53 years; range, 28-69 years) with moderate-to-severe chronic plaque psoriasis [mean Psoriasis Area and Severity Index (PASI) = 24; range, 9-42] were enrolled in the study. Concentrations of plasma MTX and that of MTXPGs in RBC were assayed using liquid chromatography methods. The area under the concentration-time curve of plasma MTX in the interval 0-8 h post-dose (AUC(0-8 h)) was measured after a test bolus dose of 10 mg, and the starting weekly dose was individualized in order to achieve the target AUC(0-8 h) of 1800 nmol.h/L. The PASI, biochemistry, and haematology tests and MTXPGs levels in RBC were evaluated at baseline and at 4-week intervals. RESULTS: The AUC(0-8 h )achieved 1360 +/- 425 nmol.h/L (mean +/- SD: range, 778-2400 nmol.h/L). The mean (range) of individualized doses was 14.5 mg/week (7.5-22.5 mg). The mean (SD) steady-state concentration of total MTXPGs observed between days 85 to 110 reached 113 (34.6) nmol/L (range, 66.1-174 nmol/L). The PASI decreased from 24.0 +/- 8.0 (mean +/- SD) at baseline to 8.0 +/- 6.1 at day 110 (P < 0.001). Thirteen patients (87%) achieved a greater than 50% improvement in baseline PASI, and seven (47%) experienced a greater than 75% improvement. There was no relationship between the percent improvement from baseline PASI and the steady-state concentration of MTXPGs in RBC. All patients tolerated MTX well. Throughout the study period, there was a continuous increasing trend in the geometric mean values of the mean corpuscular volume from 92.6 to 96.4 fL (P < 0.001) and of plasma homocysteine from 9.5 to 12.3 micromol/L (P < 0.005). The geometric mean serum alanine aminotransferase (ALT) activity slightly increased from 0.49 to 0.80 microkat/L (P < 0.05). However, only two patients had the ALT activity transiently elevated above twice the upper limit of normal. CONCLUSION: Results of this pilot trial show that the steady-state levels of MTXPGs in RBC vary less than threefold between patients and did not correlate with the change in PASI observed after 4 months of therapy with an individualised weekly dose of MTX. Whether pharmacokinetically guided dosing can improve the results of psoriasis therapy with MTX should be prospectively tested in large controlled studies.
Keywords: rozvrh dávkování léků; financování organizované; dospělí; vztah mezi dávkou a účinkem léčiva; Female; psoriáza; Adult; výsledek terapie; ženské pohlaví; Drug-Related Side Effects and Adverse Reactions; erytrocyty; lidé; Pilot Projects; Drug Administration Schedule; pilotní projekty; Treatment Outcome; stupeň závažnosti nemoci; Methotrexate; Financing, Organized; dermatologické látky; nežádoucí účinky léčiv; Dose-Response Relationship, Drug; Male; Erythrocytes; Aged; methotrexát; aplikace orální; lidé středního věku; senioři; mužské pohlaví; Administration, Oral; Severity of Illness Index; Psoriasis; Dermatologic Agents; Middle Aged; Humans